A framework to evaluate the likelihood of knowledge retention when college students obtain information from the internet. (1st January 2011) - Saleh, Zakaria I.
With the generalised use of information technologies (IT), students gather and use information from the World Wide Web and use it to complete their schoolwork and other related tasks. However, there are no indications that any of the obtained information is actually being critically thought about, or if the material is understood by the student. While the use of the internet is important for acquiring knowledge, more so, student's attitudes are also as important. This study will help better understand the student's intentions for internet use, and enable educators to determine the value of the retained knowledge. Although limited by a small student participant sample, the findings and the conclusions appear justified. These results highlight areas for further research and provide a basis for institutions to consider these associations in future policy or plan formulation for relying on the internet as an education channel. The research suggested that further research should be conducted to monitor the effect of using the internet on the learning and knowledge retention of the youngest age students group.